Aniołowie w "Apoftegmatach" Ojców Pustyni - Nocoń, Arkadiusz (Vox Patrum, 2025)
In response to the current interest in angels, the author analyses the Sayings of the Desert Fathers, that is, the most original work of monastic literature from Christian antiquity. On the basis of the facta et dicta of these experts in spiritual issues, and who were often great mystics, the author strives to present the angelology that was functioning in these circles, viz., the teaching of the monks on the nature, appearance and hierarchy of angels, and on their role in respect to God and people. He also draws attention to the specific perception of angels amongst the Desert Fathers. Summing up, the author concludes that theologically the angelology of the Desert Fathers was a continuation of the teaching of the Fathers of the Church. In an ascetic sense it perceived in angels an ideal of monastic life and assistance in its living-out in practice. Also, in an eschatological sense it brought hope and inspired a salvific optimism, because the angels – according to the Desert Fathers – are more numerous, that is, more powerful than demons who are threatening humans.